1994
DOI: 10.1182/blood.v84.4.1074.1074
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor GATA-2 is expressed in erythroid, early myeloid, and CD34+ human leukemia-derived cell lines

Abstract: To understand the functional roles that the GATA factors may play during hematopoietic cell differentiation, we examined the expression of GATA factor mRNAs and protein products in various human cell lines. Blot hybridization analyses demonstrated that GATA-1 and GATA-2 mRNAs are expressed abundantly in a set of cell lines established from human myelogenous leukemia cells, but the expression pattern of each factor is distinct. GATA-2 mRNA is expressed in all cell lines tested that express erythroid markers, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Note that PML expression affected neither the expression level of GATA-2 nor GATA-2 binding to DNA. PML-RAR␣ oncoprotein may have the potential to associate with GATA-2, which is the predominant GATA factor expressed in early myeloid progenitor cells (44,45,47) representing the cellular target for transformation in APL.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Note that PML expression affected neither the expression level of GATA-2 nor GATA-2 binding to DNA. PML-RAR␣ oncoprotein may have the potential to associate with GATA-2, which is the predominant GATA factor expressed in early myeloid progenitor cells (44,45,47) representing the cellular target for transformation in APL.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, GATA-2 has been shown to play roles in regulating proliferation of hematopoietic cells, with overexpressed GATA-2 having the ability to inhibit the cell cycle (27,53). Since GATA-2 is a predominant GATA factor expressed in early myeloid cells (44,47,48), PML may have a functional link with GATA-2 in terms of proliferation and differentiation in myeloid lineages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, in exploring the possibility that other TFs are involved in AETFC function, motif enrichment analyses of AETFC- and AEC-bound genomic sites have shown that the GATA2 motif sequence is specifically enriched at AETFC peaks relative to AEC peaks. GATA2, which is a member of the GATA family of zinc finger–containing TFs ( 48 ), has been identified as a critical regulator of hematopoietic stem cells (HSCs) during oncogenesis in the hematopoietic system. In this regard, deletion of GATA2 in Meis1a/Hoxa9-driven AML impedes maintenance and self-renewal of leukemic stem cells (LSCs) ( 49 ).…”
Section: Discussionmentioning
confidence: 99%